MENUMBUHKEMBANGKAN HUMAN DIGITAL SKILL PENDIDIK DI ABAD KE 21 - Arintina, Inda; Yarti, Rika Novi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The development of the world in the Digital Era. The role of the teacher is required to follow a generation of different technologies. The use of technology in learning is useful for facilitating quality learning. Books can be replaced with technology. Learning content is available on the internet. However, there is still a teacher's role that cannot be replaced. This is where we must strengthen the teacher as a facilitator who helps students to exploit a variety of learning resources. Teachers are able to transform themselves in the digital era,such an interest in reading. So far, various research results have shown that reading interest among teachers in Indonesia is still low, and even lacks the motivation to buy or collect books. In other words, teachers in the current information era, when involved in the internet activity, are not just downloading, but also uploading their written works that can contribute ideas to improve the quality of learning.